CASE STUDY OF APPLYING A SYMBIOTIC COMPLEX IN CHILDREN WITH CHRONIC GASTRODUODENAL PATHOLOGY - A.A. Kamalova; G.A. Khusnullina (Педиатрическая фармакология)
Chronic pathology of the gastrointestinal tract is frequently accompanied with microbiocenosis of intestines, which results in the deficiency of local and systemic protection mechanisms. This article illustrates a case study to examine the impact of a symbiotic complex on clinical manifestations, as well as characteristics of systemic endotoxinemia and antiendotoxical immunity of children with chronic gastroduodenitis. The article demonstrates that inclusion of a synbiotic containing Lactobacillus GG (LGG), Lactobacillus acidophilus, Bifidobacterium lactis, inulin, into the conventional therapy for children with chronic gastroduodenitis resulted to an earlier end of abdominal pain, dyspepsia syndrome, cystic symptoms and was accompanied with an increased level of IgA, IgM-antiendotoxin antibodies.Key words: antiendotoxin antibodies, children, endotoxin, intestinal dysbacteriosis, synbiotic.